A Growing Economy from a Buddhist Perspective - Tuladhar, Reena (Nepalese Journal of Economic Studies, 2025)
The modern global economy, often equates economic growth with materialaccumulation, but Buddhism teaches that true happiness and identity do notstem from mere materialistc possessions. Instead, it emphasizes the principle ofsufficiency, meeting one’s needs without excess. Buddhist economics, as developedby contemporary scholars, prioritizes compassion over competition and promoteswell-being over mere material gain. This paper aims to envision an alternativeeconomic model rooted in Buddhist teachings, emphasizing indicators such asGross National Happiness (GNH) and other holistic well-being indexes. Such amodel would shift the focus from increasing material wealth to addressing boththe physical and mental challenges facing humanity. That would also advocatefor economic planning that centers ecological regeneration and non-harmingprinciples. Original sources from the Pali Canon, along with recent researchby Buddhist scholars, serve as key references for this inquiry. In an increasinglyinterconnected world, economy of countries is gradually integrating with globalmarkets. As it does so, Buddhist scriptures and contemporary Buddhist economicthought offer valuable guidance for constructing a radical, values-based economicmodel tailored to countries unique socio-cultural context.